1891 Wis. Sess. Laws 61, ch. 23, § 3, pt. 28 - (:unkn) unknown (General Publisher, 1891)
Authorized the city to prohibit or regulate the carrying of any pistol, slung shot, knuckles, bowie knife, dirk, or any other dangerous weapon.
--
Keywords: CARRY